Examining Ribonucleases and G-quadruplex Binding Proteins as Regulators of Gene Expression in S. venezuelae - Mulholland, Emma (My University, 2020)
Controlling when genes are expressed is critical for the growth of an organism. Studying gene expression regulation in Streptomyces presents an opportunity to better understand how these complex bacteria develop and how they control their impressive biosynthetic capabilities. In this work we investigated the potential role of a G-quadruplex binding protein, and two ribonucleases (RNases) in regulating gene expression in Streptomyces venezuelae. G-quadruplexes are structures that form in DNA or RNA molecules. Depending on their location in DNA, G-quadruplexes can increase or decrease the expression of nearby genes and the stability of a G-quadruplex structure can be affected by G-quadruplex binding proteins. We probed the ability of a G-quadruplex-associated protein from S. venezuelae, TrmB (a tRNA-methyltransferase), to bind and methylate G-quadruplexes and prevent the formation of these structures. We were unable to conclude that TrmB bound or methylated G-quadruplex structures or motifs. RNases are enzymes that cleave RNA molecules and have important roles in controlling cellular RNA levels, and thus gene expression. We investigated the roles of RNase J and RNase III in S. venezuelae. Both of these RNases impact development and specialized metabolism in Streptomyces. We found that the RNase J mutant was unable to grow properly on classical medium containing glycerol. We also documented small RNA fragments that were unique to the RNase J mutant and sought to identify them. To better understand the RNase J and RNase III strains, we conducted RNA-sequencing of wild type S. venezuelae and mutant strains lacking RNase III or RNase J. Comparisons between each mutant and the wild type strain revealed significant changes in genes related to nitrogen assimilation, phosphate uptake, and specialized metabolite production in both the RNase III and RNase J mutant. Together these results contribute to our understanding of the diverse regulatory features that exist in S. venezuelae.
Keywords: Microbiology; Gene Regulation; Molecular Genetics